SECURING THE ZAMRUD NATIONAL PARK BASED ON THE TRADITIONAL FISHERMAN COMMUNITY - Hesti Asriwandari; Rina Susanti; Yoskar Kadarisman (Sosiohumaniora, 2021)
The Zamrud Area is designated as a National Park through the Decree of the Minister of Environment and Forestry No. 350/ Menlhk/Setjen/PLA.2/5/2016 Year 2016. Within this area there are two lakes namely Pulau Besar Lake and Bawah Lake and have a diversity of flora and fauna. In the area of the Zamrud National Park, there are fishing communities who have been fishing for generations since the 70s, “mandah” and living in the area, and are involved in guarding and protecting the area from the threat of illegal logging and protected bird catching. The research approach used is qualitative. Research informants were taken based on criteria, namely to obtain a complete picture of the actions of traditional fishermen in securing and protecting the Zamrud National Park. The results showed that the forms of security measures taken by traditional fishermen in preserving the Zamrud National Park were: 1) Conducting river patrols, 2) Disseminating regional regulations, 3) Reprimanding visitors who violated the law, 4) Reporting violations and special incidents to the Forest Police. and BKSDA Riau. In an effort to maintain and maintain the sustainability of fishing activities in the Pulau Besar and Bawah Lake areas, traditional fishermen do: 1) Limit the use of fishing gear, 2) Limit the number and types of catches (not catching fish that are prohibited), 3) Maintain Lakeside Vegetation, 4) Not clearing land and taking forest products in the form of wood, and 5) Cooperating with various parties such as the local government.